The Black studies reader - Bobo, Jacqueline; Hudley, Cynthia; Michel, Claudine (Routledge, 2004)
Black studies emerged from the tumultuous social and civil rights movements of the 1960s and empowered African Americans to look at themselves in new ways and pass on a dignified version of Black history. However, it also enriched traditional disciplines in profound and significant ways. Proponents of Black and ethnic studies confronted the false notion that scholarly investigations were objective and unbiased explorations of the range of human knowledge, history, creativity, artistry, and scientific discovery. As they protested against hegemonic notions like universal psychology and re-evaluated canonical texts in literature, a new model of academic inquiry evolved: one committed to serving a range of populations, that critiqued traditional politics, culture, and social affairs, and worked with activist energy for the transformation of the existing social order. With an all-star cast of contributors, The Black Studies Reader takes on the history and future of this multi-faceted academic field. Topics include Black feminism, cultural politics, Black activism, lesbian and gay issues, African American literature and film, education, and religion. This authoritative collection takes a critical look at the current state of Black studies and speculates on where it may go from here.
Keywords: LGBTQIA2+; afro-féminisme; amériques; approches et analyses; féminisme islamique; histoire et politique; identités LGBTQIA2+; militance; outils; ouvrages de références; racisme; ressource en ligne; régions géographiques; sexualité; système colonial; systèmes d'oppressions; thématiques; états-unis

Encyclopedia of feminist literature - Whitson, Kathy J. (Greenwood Press, 2004)
A reference guide to the history and development of feminist literature, this book covers a wide range of works and genres, including novels, short stories, poetry, plays, and criticism. It focuses on the feminist works from writers such as Willa Cather, George Eliot, and Helen Keller.
Keywords: arts; cours; cycles supérieurs; discipline; fem7000; genre; identités LGBTQIA2+; outils; ouvrages de références; ressource en ligne; thématiques; études littéraires